One-pot Diels–Alder cycloaddition/gold(I)-catalyzed 6-endo-dig cyclization for the synthesis of the complex bicyclo[3.3.1]alkenone framework - Sow, Boubacar; Bellavance, Gabriel; Barabé, Francis; Barriault, Louis (Beilstein Journal of Organic Chemistry, 2011)
The rapid synthesis of bicyclo[m.n.1]alkanone cores possessing quaternary carbon centers adjacent to a bridged ketone represents a significant synthetic challenge. This type of architectural feature is embedded in various complex biologically active compounds such as hyperforin and garsubellin A. Herein, we report a highly diastereoselective one-pot Diels–Alder reaction/Au(I)-catalyzed carbocyclization to generate bicyclo[3.3.1]alkanones in yields ranging from 48–93%.
Keywords: bicyclo[3.3.1]nonenone; carbocyclization; Diels–Alder; gold catalysis; one-pot process